THE USE OF SEDAYU METHOD IN LEARNING THE QURAN IN EARLY CHILDHOOD - Abdul Rosid; Munzier Suparta; Romlah Abubakar Askari (Advances In Social Humanities Research, 2023)
One of the mandates Allah SWT gives to both parents is the presence of a child, soulmate, heartmate and solace for both. The presence of a child is a great hope for both parents. Therefore, the key to a child's future success lies in the seriousness of both parents in maintaining and educating the trust seriously. In line with that, the fundamental and main form of mandate is to instill religious education in children from an early age so that they grow and develop into human beings with character and also become religious and independent individuals. This research intends to answer the problem: What and how is the Sedayu method as a method of learning the Quran? The data analysis technique in research, namely by using descriptive techniques by making a picture is carried out by collecting data, reducing data, presenting data, and concluding. The conclusion that the author gets is as follows: The Sedayu method is one of the methods among the methods in Indonesia. This method was created to assist in learning the Quran, especially recognizing letters for early childhood at PPQS Nurani Sasak Tengah, Bogor.